Dampak Bantuan Pangan Non Tunai terhadap Konsumsi Makanan dan Rokok pada Rumah Tangga Miskin di Indonesia - Istriawati, Nina; Dartanto, Teguh (Mahesa Research Center, 2022)
This article aimed to determine the extent to which the BPNT program affects food consumption, nutritional intake, and cigarettes in poor households in Indonesia. The problem was focused on comparing the impact of social assistance in the form of in kind, e-vouchers, and cash transfers on changes in consumption of calories, protein, fat and carbohydrates in poor households receiving assistance. Some Researches in a number of countries showed that in-kind assistance is able to have the greatest impact on increasing the beneficiary's calorie consumption compared to cash transfers. This research was analyzed quantitatively using a quasi-experimental design approach with the Propensity Score Matching (PSM) analysis method. Sources of data came from secondary data from the National Socio-Economic Survey (Susenas) Quarter I (March) of the Central Statistics Agency (BPS) 2018, in the form of the consumption/expenditure module (KP), and the Susenas of basic information on household members (KOR). The result showed that BPNT contributes to an increase in the fat consumption of beneficiary households. The biggest increase occurred in the BPNT PKH complementary program, not only in fat consumption, but also in protein. BPNT also contributed to the increase in cigarette consumption among households in the non-PKH and PKH program group, while in the PIP program group, showed the opposite result.